Exploring possible relationships between 25(OH)D deficiency and variables related to inflammation, endothelial function, and enzymatic antioxidants in adolescent athletes: a prospective study - Evdokia Varamenti; Anissa Cherif; Zoran Nikolovski; Montassar Tabben; Athanasios Z. Jamurtas; Marco Cardinale (Biology of Sport, 2019)
Although the role of vitamin D in calcium and bone metabolism is well documented, there is little clarity regarding the implications of low vitamin D status for inflammation, endothelial function, and antioxidant status in adolescent athletes. A prospective cohort study was conducted, and 44 male adolescent athletes, training at a sports academy in the Middle East, were assigned to either the intervention group (VitDs), consisting of vitamin D deficient athletes [twenty-five hydroxyvitamin D (25(OH)D) 30 ng/ml; n = 22]. Vitamin D status, inflammatory cytokines, endothelium-related variables, and antioxidant enzymes were measured twice during a nine-week training period. At the baseline, the athletes in the VitDs group had significantly lower concentrations of 25(OH)D, vascular endothelial growth factor (VEGF), and glutathione peroxidase (GPx), and higher levels of parathyroid hormone (PTH), interleukin-6 (IL-6), interleukin-1 receptor antagonist (IL-1ra), and nitrite (NO2) (p < 0.05), in comparison to the athletes in the sufficient group. After vitamin D supplementation for the VitDs group, the two cohorts differed considerably in vitamin D binding protein (VDBP) and PTH concentrations (p < 0.05). Our data suggest that the low levels of vitamin D possibly induced alterations in the investigated biochemical parameters of athletes in the VitDs group at the beginning of the monitoring period. Furthermore, while the vitamin D supplementation was effective in increasing 25(OH)D status, it may have concurrently positively influenced variables that are related to inflammation, endothelial function, and enzymatic antioxidants.